The association of different progesterone preparations with preterm birth prevention. (18th October 2019) - Krispin, Eyal; Hadar, Eran; Chen, Rony; Wiznitzer, Arnon; Kaplan, Boris
Abstract: Objective: We aimed to compare the efficacy of commonly available progesterone preparations for preterm birth prevention. Methods: A retrospective cohort study of all women treated with progesterone to prevent preterm birth and delivered in a single university-affiliated tertiary medical-center. Four progesterone preparations were compared: vaginal Endometrin 100 mg twice daily, vaginal Crinone 8% gel 90 mg daily, vaginal Utrogestan 200 mg daily, and intramuscular 17α-hydroxyprogesterone caproate (17-OHPC) 250 mg weekly. All women were considered at risk for preterm birth according to: prior preterm birth or cervical length below 25 mm measured during the second trimester. Significant maternal morbidity, pregnancy achieved by artificial reproductive technique and cerclage placement were excluded. Primary outcome was the rate of preterm birth prior to 37 weeks of gestation. Results: Overall, 422 women were allocated to four study groups according to progesterone preparation: Endometrin 175 (41.5%), Crinone 73 (17.3%), Utrogestan 154 (36.5%), and 17-OHPC 20 (4.7%). Rates of preterm birth prior to 37 gestational weeks were lowest on the Endometrin treatment group (12.6 versus 20.5, 17.5, and 35% in the rest, p = .05). Multivariate analysis revealed that the progesterone preparation was associated with preterm birth prior to 37 gestational weeks (LR = 8.3, p = .004). The need for maternal red blood cells transfusion was significantly higher in the Endometrin subgroup (4% versus 0 in all others, p = .018). This finding remained significant after adjustment to potential confounders (LR 16.44, p < .001). Neonatal outcomes did not differ between groups. Conclusions: Different progesterone preparations prescribed to women at risk, may possess different efficacy in preventing preterm delivery prior to 37 weeks of gestation.